2014
DOI: 10.1136/jech-2014-204271
|View full text |Cite
|
Sign up to set email alerts
|

The effect of participatory women's groups on infant feeding and child health knowledge, behaviour and outcomes in rural Bangladesh: a controlled before-and-after study

Abstract: BackgroundDespite efforts to reduce under-5 mortality rates worldwide, an estimated 6.6 million under-5 children die every year. Community mobilisation through participatory women's groups has been shown to improve maternal and newborn health in rural settings, but little is known about the potential of this approach to improve care and health in children after the newborn period.MethodsFollowing on from a cluster-randomised controlled trial to assess the effect of participatory women's groups on maternal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(60 citation statements)
references
References 22 publications
1
58
1
Order By: Relevance
“…A randomized controlled trial in Kenya found that women who received intensive home-based breast-feeding counselling addressing prevention and management of breast-feeding challenges were more likely to exclusively breast-feed than women who received semi-intensive counselling at a health facility (93) . In a cluster-randomized controlled trial carried out in Bangladesh, the implementation of participatory women's groups led to significant increases in EBF for 6 months (15 %) and mean duration of breast-feeding (+38 d) in intervention v. control areas and pre-v. postintervention (92) . Similarly, in India, peer counselling through mother support groups showed improved initiation within an hour of birth, EBF and decreased prelacteal feeding at 2 and 5 years post-baseline (94) .…”
Section: Promising Interventions and Programmatic Implications Of Thementioning
confidence: 99%
See 1 more Smart Citation
“…A randomized controlled trial in Kenya found that women who received intensive home-based breast-feeding counselling addressing prevention and management of breast-feeding challenges were more likely to exclusively breast-feed than women who received semi-intensive counselling at a health facility (93) . In a cluster-randomized controlled trial carried out in Bangladesh, the implementation of participatory women's groups led to significant increases in EBF for 6 months (15 %) and mean duration of breast-feeding (+38 d) in intervention v. control areas and pre-v. postintervention (92) . Similarly, in India, peer counselling through mother support groups showed improved initiation within an hour of birth, EBF and decreased prelacteal feeding at 2 and 5 years post-baseline (94) .…”
Section: Promising Interventions and Programmatic Implications Of Thementioning
confidence: 99%
“…The success of large-scale IYCF programmes lies in the importance of IYCF counselling and community support, in tandem with community awareness (90) . Several randomized controlled trials have demonstrated that community-led interventions, with an attention to quality, content and frequency of counselling, show positive effects on EBF (91,92) . A randomized controlled trial in Kenya found that women who received intensive home-based breast-feeding counselling addressing prevention and management of breast-feeding challenges were more likely to exclusively breast-feed than women who received semi-intensive counselling at a health facility (93) .…”
Section: Promising Interventions and Programmatic Implications Of Thementioning
confidence: 99%
“…Despite no changes in care-seeking, there were significant improvements in mothers’ knowledge of disease prevention and management, including giving anthelminthics, danger signs and handwashing at critical times. Reduced maternal reports of under 5 years' morbidities and duration of illness were also observed 10. Significant increases were also seen in the intervention group for both exclusive breast feeding for at least 6 months, and the mean duration of breast feeding 10.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, verbal autopsy data from the trial suggest that reductions in deaths due to neonatal infections may have largely contributed to impacts on neonatal mortality. Formative evaluation of the PWG intervention on postneonatal child health in a subset of groups supports a link with improved hygiene 10. Despite no changes in care-seeking, there were significant improvements in mothers’ knowledge of disease prevention and management, including giving anthelminthics, danger signs and handwashing at critical times.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation